2017
DOI: 10.1063/1.4975056
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of Si-doped GaN prepared using pulsed sputtering

Abstract: In this study, we investigated the basic electrical properties of Si-doped wurtzite GaN films prepared using a low-temperature pulsed sputtering deposition (PSD) process. We found that the electron concentration can be controlled in the range between 1.5 × 1016 and 2.0 × 1020 cm−3. For lightly Si-doped GaN ([Si] = 2.1 × 1016 cm−3), the room temperature (RT) electron mobility was as high as 1008 cm2 V−1 s−1, which was dominantly limited by polar optical phonon scattering. Moreover, we found that heavily Si-dope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 25 publications
2
43
0
Order By: Relevance
“…In addition, α is a measure of how rapidly the mobility increases from µ min to µ max with decreasing doping level. This model has been proved to describe the dependence of mobility on carrier density in wide‐gap semiconductors . Fitting Eq.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, α is a measure of how rapidly the mobility increases from µ min to µ max with decreasing doping level. This model has been proved to describe the dependence of mobility on carrier density in wide‐gap semiconductors . Fitting Eq.…”
Section: Resultsmentioning
confidence: 99%
“…The details of the growth procedure have been reported elsewhere. 12,13 To investigate their electrical properties, we deposited the n-type doped GaN epilayers onto commercially available semi-insulating C-doped GaN templates on sapphire as starting substrates. The dislocation density of the GaN templates was typically 5.0 × 10 9 cm 2 .…”
mentioning
confidence: 99%
“…[ 7 ] PSD provides a wider range of doping capabilities compared to conventional techniques such as MOCVD and molecular beam epitaxy. [ 8–10 ] We investigated the electron transport properties of PSD‐grown n‐type AlN on sapphire with a high Si‐doping level above 10 19 cm −3 and reported that Si‐doped AlN yielded clear n‐type conductivity and electron mobility of 44 cm −2 V −1 s −1 . [ 11 ]…”
Section: Introductionmentioning
confidence: 99%